2014
DOI: 10.1097/dcr.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BMI on Outcomes in Proctectomy

Abstract: Background The unique surgical challenges of proctectomy may be amplified in obese patients. We examined surgical outcomes of a large, diverse sample of obese patients undergoing proctectomy. Objective To determine whether increased body mass index is associated with increased complications in proctectomy. Design A retrospective review of the American College of Surgeons National Surgical Quality Improvement Program database (2010 and 2011). Patients Patients undergoing non-emergent proctectomy, excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…This is in accordance with the results of our multivariate analysis. In contrast to many other studies, our results did not show an increased mortality for underweight patients [3,5,13,15,17]. Adequate selection of patients for surgery and sufficient management of complications in case of their occurrence are possible reasons for this specific result.…”
Section: Impact Of Underweightcontrasting
confidence: 98%
See 3 more Smart Citations
“…This is in accordance with the results of our multivariate analysis. In contrast to many other studies, our results did not show an increased mortality for underweight patients [3,5,13,15,17]. Adequate selection of patients for surgery and sufficient management of complications in case of their occurrence are possible reasons for this specific result.…”
Section: Impact Of Underweightcontrasting
confidence: 98%
“…In our study, the physical status (ASA) was worse in those patients, which also showed more comorbidities, especially cardiovascular risk factors and diabetes mellitus (data not shown). These findings are not surprising and have been widely described in the literature [2,[13][14][15].…”
Section: Impact Of Obesitysupporting
confidence: 77%
See 2 more Smart Citations
“…18, 19 Included were non-emergent ileal pouch-anal anastomosis procedures (CPT codes 44158, 44211, 45113, and 44157) performed by general and colorectal surgeons at NSQIP-participating hospitals. Recorded postoperative diagnoses were categorized as cancer, inflammatory bowel disease (IBD), or “other,” when cancer or IBD were not explicitly specified.…”
Section: Methodsmentioning
confidence: 99%